Symbolism In D. H. Lawrence's Women In Love - Pratiwi, Suci Yuli (2004)
The objective of this study is to reveal the significance and the meaning of symbols implied in D. H. Lawrence's Women in Love. In order to reach the answer, the writer employs the theory of symbolism in literature together with the implication. The study employs a qualitative method. This study uses library data that are characterized into two, namely the primary and secondary data. The primary data source and the object of study is the novel Women in Love itself, meanwhile the secondary one is any literature related with this study. The data collections are gained from both, primary and secondary data source in sort of document as evidence. The study uses study research to collect the data. The collected data are analyzed by means of descriptive and hermeneutic analysis. The outcome of this study affirms that the novel of Women in Love is full of symbolism that can be seen through the reflection of the character, setting, action, object, plot, and style. Women in Love describes English society who tries to define their self-actualization in their effort in transcending the difficulties of the modern life in the beginning of the twentieth century. D. H. Lawrence creates the story as a form of his commentary, allusion, and criticism to the continuous upheavals in the society and also England's degenerating process in all forms of life.